Intra- and interspecific competition between glyphosate-resistant and susceptible junglerice (Echinochloa colona) populations and soybean - Picapietra, Gabriel (2025)
Herbicide-resistant weeds demand particular attention in the selection of management strategies, considering the characteristics and fitness differences between susceptible and resistant plants. This study aimed to analyze two heterogeneous junglerice populations, glyphosate-susceptible (EC-S) and glyphosate-resistant (EC-R), derived from field-collected seeds, to quantify the productivity of EC-S and EC-R, to analyze the impact of soybean plants, and to evaluate density dependence. Experiments were conducted in a growth chamber using plastic pots, combining three factors: junglerice density (2, 4, and 8 plants pot−1), the proportion of EC-S and EC-R (100% EC-S, 50% EC-S:50% EC-R, 100% EC-R), and soybean density (0 and 1 plants pot−1). One-leaf junglerice seedling and soybean seeds were planted in plastic pots. After 65 d, plant height (PLH), total number of tillers (TIL), seed number (SEN), seed weight (SEW) per plant, weight of 100 seeds (HSW), and aboveground dry matter (ADM) were measured. The variables measured were affected primarily by junglerice density and the presence of soybean. Vegetative and reproductive structures of EC-S and EC-R exhibited strongly density-dependent patterns. One soybean plant increased (P < 0.05) junglerice productivity at low densities but had no effect at high densities (8 plants pot−1). Mostly EC-S and EC-R showed the same competitive ability. However, EC-S presented a higher index of competitive ability than EC-R in SEN and SEW at lower densities with a soybean plant. A resource complementarity (RYT ∼ 1) between EC-S and EC-R was observed (P < 0.05), regardless of the presence of the crop. These results demonstrate that, even in the absence of glyphosate, fitness differences favor heterogeneous resistant populations. This highlights the inherent adaptive advantage of resistant populations and, considering the extensive reliance on glyphosate in current production systems, underscores the urgent need for integrated weed management strategies to mitigate the evolution and spread of resistant populations.